Use of granulocyte transfusions among haematology units in England and North Wales. Issue 3 (18th August 2017) - Morton, S.; Mijovic, A.; Marks, D. I.; Griffin, J.; Massey, E.; Bhatnagar, N.; Stanworth, S. J.
SUMMARY: Objectives: To establish the current use of granulocyte transfusions in haematology patients and explore interest in further research. Background: Granulocytes may be used for the treatment of severe infection in neutropenic patients or for primary or secondary prophylaxis. Clinical utility of granulocyte transfusions is unclear, and recent studies have demonstrated equivocal outcomes. Pooled granulocytes are the main granulocyte product used in England and Wales, but there are no data on the patterns of use and little consensus on accepted indications. Methods: A survey was distributed to UK hospitals delivering intensive chemotherapy. Clinical scenarios were posed, with further questions on clinician experience of using granulocytes, availability of the product, barriers to use and interest in further research. Results: The response rate was 57%; 34·9% of all responses were from allogeneic stem cell transplant centres. Paediatric centres comprised 9·5% respondents, and 19% centres had access to apheresis granulocytes. Of respondents, 58·7% had used granulocytes in the last 3 years, 89·2% of whom used granulocytes to treat refractory infection. There was little consensus on use of granulocytes in the given clinical scenarios even when patients clearly met national guideline criteria. Paediatric centres were overall more likely to recommend granulocyte use. The most frequently identified barrier to use of granulocytes was lack of evidence of effect. Of the respondents, 75% indicated a willingness to participate in further research. Conclusion: There remains a lack of consistency about use of granulocytes, which is unsurprising given the lack of clinical data to support their efficacy. We did, however, demonstrate a willingness to participate in further research.